Evaluation of Serum ANGPTL8/Betatrophin and Cartonectin/CTRP3 Levels in Diabetic and Non-Diabetic Retinopathy - Pehlivan, Vehbi; Gursu, Mehmet Ferit; Citak, Onur; Onalan, Erhan; Yakar, Burkay; Donder, Emir (Coll Physicians & Surgeons Pakistan, 2023)
Objective: To determine serum betatrophin and cartonectin levels and their relationship with biochemical parameters in diabetic and non-diabetic retinopathy.Study Design: Descriptive study.Place and Duration of Study: Department of Internal Medicine and Ophthalmology, School of Medicine, Firat University, Turkey, from April to November 2020.Methodology: Patients with diabetic retinopathy (DR), non-diabetic retinopathy (non-DR), type 2 diabetes mellitus without retino-pathy, and healthy controls, were enrolled from April to November 2020. Demographic, metabolic, and biochemical parameters were evaluated. Serum betatrophin, cartonectin, IL-6, and TNF alpha levels were assayed by ELISA methods. One-Way Anova or Kruskal Wallis tests were applied to find out statistical significance among different variables between four groups.Results: A total of 84 participants (DR= 21 patients; non-DR= 21 patients; 21 diabetic patients without retinopathy and 21 healthy controls) were enrolled in the study. TNF-alpha level was significantly higher in both DR and non-DR than in controls (p<0.001). IL-6 level was higher in DR group than T2DM and controls (p=0.013). Serum betatrophin level was significantly higher in DR group than in non-DR and T2DM groups (p=0.002). Cartonectin level was decreased in DR, non-DR, and T2DM groups compared to non-diabetic healthy controls (p=0.002).Conclusion: Serum betatrophin levels are higher in DR, whereas cartonectin levels are lower in both DR and non-DR groups. Serum betatrophins and cartonectin estimation may be helpful in early diagnosis and differential diagnosis in cases of diabetic and non-dia-betic retinopathy.
Keywords: Angiopoietin-like protein 8; Cartonectin; CTRP3; Diabetic retinopathy; Diabetes mellitus; Type 2; Diagnosis; Differential; Betatrophin